In the crucible of empire (Leuven ; Paris ; Bristol, CT)
vi, 337 sayfa
Keywords: “This volume examines the dynamic concept and changing reality of Roman citizenship from the perspective of the provinces in Rome's vast, multi-ethnic empire, both before and after Caracalla's grant of universal citizenship in 212 CE. In Greek communities, and in Jewish and Christian conceptual and actual constructed communities, the Roman definition of citizenship had a profound impact on the shape of abstract ideas of community, discourse about communal membership and peoplehood, and legal and civic models. Just as Roman citizenship was forever redefining its restrictions and becoming ever-more inclusive, so the borders of the other communities to which Greeks, Christians and Jews claimed “citizenship” were also flexible, adaptable, dynamic.” --